The Effectiveness Of The Mind Mapping Method On Learning Achievement Of Islamic Cultural History In Class VIII Students Of Mtsn Kepulauan Selayar - Nurul Qalbi; Syamsuddin; Muhammad Rusmin B; Saprin; Muhammad Yahdi (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
This study aims to determine the effectiveness of the mind mapping method in improving student learning achievement in the subject of Islamic Cultural History (SKI) for grade VIII at MTsN Kepulauan Selayar. This study was motivated by the low learning achievement of students in the subject of Islamic Cultural History (SKI), especially in memorization materials. The study used a quantitative approach with an experimental research type through the One Group Pretest-Posttest Design. The study population was 36 grade VIII students. Data collection techniques were carried out through tests and documentation, while data analysis used the Normalized Gain (N-Gain) test. The results showed that the average pre-test score of students was 58.33, increasing to 81.53 in the post-test, with an average increase of 23.20. The results of the N-Gain test obtained an average score of 56.34% which is in the moderate category. These findings indicate that the application of the mind mapping method is quite effective in improving student learning achievement in the subject of SKI. Theoretically, the mind mapping method supports the cognitive learning process through concept visualization, the use of keywords, colors, and relationships between ideas, making it easier for students to understand and remember material more systematically. In addition to improving learning outcomes, this method also creates a more active, interactive, and student-centered learning environment. Therefore, the mind mapping method can be used as an innovative learning alternative to improve the quality of Islamic Cultural History instruction.